2022
DOI: 10.3390/ijerph19137612
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 Pandemic on Dietary Consumption among Chinese Residents: Evidence from Provincial-Level Panel Data

Abstract: The COVID-19 pandemic has profoundly affected people’s daily lives, including their dietary behaviors. Using a panel data set of 31 provinces from 2015 to 2020, this study employed two-way fixed effects (FE) models to examine the impacts of the COVID-19 pandemic on dietary consumption among Chinese residents. The results showed that the COVID-19 pandemic positively affected residents’ consumption of grain, eggs, dairy, and white meat (poultry and aquatic products), while it had a negative effect on individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Compared with the physical activity of Chinese individuals during the non-pandemic period (14.1%) reported by WHO, the prevalence of insufficient physical activity rose over three-fold (57.5%) during the pandemic [ 14 ]. Zheng et al (2022) discussed the impacts of the COVID-19 pandemic on diet among Chinese citizens [ 15 ]. Zhu et al (2021) found a significant increase in total food intake (9.8%) and a significant decrease in PA (31.5%) during lockdowns in Wuhan [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the physical activity of Chinese individuals during the non-pandemic period (14.1%) reported by WHO, the prevalence of insufficient physical activity rose over three-fold (57.5%) during the pandemic [ 14 ]. Zheng et al (2022) discussed the impacts of the COVID-19 pandemic on diet among Chinese citizens [ 15 ]. Zhu et al (2021) found a significant increase in total food intake (9.8%) and a significant decrease in PA (31.5%) during lockdowns in Wuhan [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The highest increase in the Healthy Eating Index during the lockdown was shown among the less-educated participants in a Canadian study [28]. Favourable changes in food consumption induced by the COVID-19 pandemic were more prominent for Chinese residents who lived in rural areas than urban areas [29]. A Spanish study found that people who lived in rural areas during the quarantine were more physically active than those who lived in urban areas were [30].…”
Section: Discussionmentioning
confidence: 94%
“…A total of 13 studies that included national data were extracted for details ( Table 4 ). Of a total of 13 studies, 6 studies were performed in China, 37 , 38 , 39 , 40 , 41 , 42 2 in Vietnam, 43 , 44 2 in Japan, 45 , 46 1 in South Korea, 47 1 in Malaysia 48 and 1 in New Zealand. 49 …”
Section: Covid-19 Effects On the Changes Of Dietary Behaviourmentioning
confidence: 99%
“…analysed provincial level food consumption data between 2015 and 2020 and found that rural residents and those living in the eastern region were more likely to adopt a healthier diet due to the COVID-19 pandemic. 37 In Japan, perceived threat of COVID-19 has been found to be positively associated with both healthier and unhealthier dietary changes with odds ratios (OR) of 1.06 (95% CI 1.04–1.07) and 1.02 (1.00–1.04), respectively. 46 Surprisingly, decrease in household income also affected dietary change in both directions with ORs of 1.42 (1.18–1.70) and 1.53 (1.20–1.95) for healthier change and unhealthy change.…”
Section: Covid-19 Effects On the Changes Of Dietary Behaviourmentioning
confidence: 99%